تدابير الطوارئ الصحية المتخذة لمواجهة جائحة كوفيد-19 ما بين اعتبارها حالة ضرورة لتعزيز وحماية الحق في الصحة وانتهاك الحقوق والحريات العامة: دراسة مقارنة - عبدالله، محمد أحمد عبدالله (المركز العربي للأبحاث والدراسات الإعلامية, 2020)
أدى تفشي جائحة كوفيد 19– إلى توقف كبير في مظاهر الحياة العامة والى إحداث جملة من التأثيرات الاقتصادية والاجتماعية والسياسية، وتم العمل في بعض الدول وفقا لقوانين استثنائية أو سن قوانين طوارئ جديدة والتي أحدثت حالة من الجدل، فتم فرض حالة الطوارئ وحظر التجوال وعزل مدن ومناطق كاملة، وتوقفت كثير من وسائل الإعلام وقيدت حركة النقل وخرجت قطاعات مهمة من دائرة الإنتاج، مما كان لها الأثر الأكبر على الحقوق والحريات العامة. إلا أن هذه الإجراءات كانت ضرورية ومطلوبة للحد من الانتشار السريع لهذا الفيروس باعتبار أن حالة الطوارئ امر ضروري فرضه انتشار الفيروس وتهديده للمجموعة البشرية، وبالتالي يعتبر نظام استثنائي تتفق فيه مختلف الأنظمة القانونية على كفالة الحق للدولة في الحد من بعض الحقوق والحريات بغية الحفاظ على امن الأشخاص وسلامتهم. هدفت الدراسة إلى توضيح تدابير الطوارئ الصحية المتخذة لمجابهة جائحة كوفيد 19-في مختلف المجالات والأنشطة، لا سيما التدابير الماسة بالحقوق والحريات العامة، ومدى اعتبار انتشار فيروس كوفيد 19– حالة ضرورة تقتضي اتخاذ تدابير استثنائية من قبل الدول، وبيان مدى التوفيق بين مقتضيات اتخاذ تدابير طوارئ صحية للحد من انتشار الفايروس وضمان حماية الحقوق والحريات باعتبارها من واجبات الدولة. وعالجت الدراسة إشكالية البحث من خلال الاستعراض والتحليل في مدى تأثير التدابير الطوارئ الصحية على جوهرِ الحقوقِ المتأصلةِ في الشخصِ الإنساني، وضرورة التوفيق والتناسب بين تعزيز الحق في الصحة وحماية الحقوق والحريات العامة.
The outbreak of the Covid-19 pandemic led to a major halt in public life and to a host of economic, social and political impacts, and some countries were working according to exceptional laws or enacting new emergency laws that caused a state of controversy, so a state of emergency was imposed, curfews, and cities and regions isolated Many media outlets stopped, transportation was restricted, and important sectors left the production circle, which had the biggest impact on public rights and freedoms. However, these measures were necessary and required to curb the rapid spread of this virus, given that the state of emergency is a necessity imposed by the spread of the virus and its threat to the human group, and thus it is considered an exceptional system in which the various legal systems agree to guarantee the state's right to limit some rights and freedoms in order to preserve the security of people. And their safety. The study aimed to clarify the health emergency measures taken to confront the Covid-19 pandemic in various fields and activities, especially measures affecting public rights and freedoms, and the extent to which the spread of the Covid-19 virus is considered a necessity that requires taking exceptional measures by countries, and to indicate the extent to which the requirements of taking measures are reconciled. Health emergencies to limit the spread of the virus and ensure protection of rights and freedoms as it is one of the duties of the state. The study addressed the problem of research through review and analysis of the impact of health emergency measures on the essence of the inherent rights of the human person, and the need for reconciliation and proportionality between promoting the right to health and protecting public rights and freedoms.
Keywords: الأوبئة العالمية -- فيروس كورونا "كوفيد-19" -- الطوارئ الصحية -- التدابير الصحية -- حقوق الإنسان